1980
DOI: 10.1103/physrevlett.45.1035
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and Disorder in Arrays of Point Contacts

Abstract: Since the early work of London 1 supercurrents and the penetration depth of superconductors appear as manifestations of phase coherence, or order in momentum space, among the superconducting electrons. Similarly Josephson currents and penetration depth result from phase correlations between superconductors separated by a barrier. By the same token, one may expect intuitively that an array of a great number of junctions (such as a granular superconductor) will display supercurrents and static screening of exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…It appears also that for d ≥ 4, υ dc = 0, which means that above dimension 4, the present SCA acts exactly like the MFT, whereas it predicts correctly the universal quantities for dimension 4 transitions, one at T c where the system becomes superconducting and locks to produce a state with very short-range phase coherence and the second at T * c < T c , where the superconducting phase locks to produce a state with long-range phase coherence. Only the lower transition is a true phase transition, with a divergent correlation length [36,37,38,39]. In 3D systems, the scaled width υ 3c = δTc Tc is of the order of 10 −14 to 10 −10 , much too small to be accessible experimentally.…”
Section: Model Formulation and Renormalized Gaussian Approachmentioning
confidence: 99%
“…It appears also that for d ≥ 4, υ dc = 0, which means that above dimension 4, the present SCA acts exactly like the MFT, whereas it predicts correctly the universal quantities for dimension 4 transitions, one at T c where the system becomes superconducting and locks to produce a state with very short-range phase coherence and the second at T * c < T c , where the superconducting phase locks to produce a state with long-range phase coherence. Only the lower transition is a true phase transition, with a divergent correlation length [36,37,38,39]. In 3D systems, the scaled width υ 3c = δTc Tc is of the order of 10 −14 to 10 −10 , much too small to be accessible experimentally.…”
Section: Model Formulation and Renormalized Gaussian Approachmentioning
confidence: 99%
“…A quasi-equilibrium (critical state) is established (Bean 1962) where the pinning force density is equal to the gradient of the local magnetic flux pressure such that at each point in the material (Kim et al 1962) 14~(CUrlH) XIlH I = O(H). (1) Here, H(r) is the local magnetic field obtained by averaging the meandering vortex lines over a volume containing a large number of grains, and 11 is the effective permeability of the medium due to the diamagnetism of the grains, representing the fraction of the sample which is in a non-Meissner state (Raboutou et al 1980).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…2(c). It is found that the critical current exhibits a linear relationship with respect to magnetic field, the phenomena may be related to the existence of the defects within the grains 17,18 connectivity 19,20 in YBCO film. The measurement was carried out several times, the results are reproducible.…”
mentioning
confidence: 92%